ENSURING ACCURATE INFORMATION FROM WITNESSES: THE ROLE OF COGNITIVE INTERVIEW AND ENHANCED COGNITIVE INTERVIEW TECHNIQUES IN FINANCIAL FORENSICS - Eisenberg , Paul (International Journal of Current Practice in Management and Leadership (IJCPML), 2022)
The cognitive interview (CI) and enhanced cognitive interview (ECI) techniques were developed in the 1980s and 1990s, respectively, with the aim of improving witness memory recall compared to the standard interview (SI) approach. However, the efficacy of these techniques remains controversial, and the complexity of human memory and psychology poses challenges in determining the most effective approach. This paper presents a literature review of previous research on CI and ECI techniques and evaluates these techniques in light of vulnerable witnesses such as children, persons with intellectual disabilities, and the elderly. The review found that the CI and ECI techniques are more effective in obtaining more accurate information from both invulnerable and vulnerable witnesses, except for interviewees with autism spectrum disorder (ASD). However, the CI and ECI techniques require proper training and the development of social skills, which can be challenging for investigators to apply. Thus, more educative efforts are in order to establish the CI/ECI approaches among investigation officers.